CRYOPRESERVATION OF PEAR MERISTEMATIC TISSUES - Turdiyev , Т.Т.; Frolov , S.N.; Madiyeva , G.А.; Rymkhanova , N.K.; Kovalchuk , I.Yu. (Eurasian Journal of Applied Biotechnology, 2017)
The southern and south-eastern regions of Kazakhstan have exceptionally favorable conditions for the cultivation of pear. However, in recent years, the areas occupied with this culture are gradually decreasing. Many foreign and domestic cultivars, valuable hybrids and local traditional cultivars of folk breeding carrying genes of high productivity and adaptability have been lost in the field genebanks (orchards and nurseries). It is necessary to study, collect and preserve valuable genotypes that have important economic and biological characteristics to restore and prevent further loss of the gene pool. Conservation of plant genetic resources in the field is associated with significant financial costs for the care of plantations, as well as the risk of loss of cultivars due to disease, pests and adverse environmental factors. The most promising and effective approach to solve this problem is the cryopreservation of plant germplasm in liquid nitrogen. Studies on optimization of cryopreservation protocols for pear meristematic tissues were carried out based on vitrification method with 0.3 M sucrose. It has been established that the viability of meristematic tissues after cryopreservation depends on the duration of hardening, the method of thawing, the type of cryoprotectant and genotype. Optimum duration of hardening by variable temperatures (8 h, 22°C, light 5.9 lx, then 16 h, –1°C, dark) is 3-4 weeks, and the best cryoprotectant in preparing apical meristems for cryopreservation is PVS2. An effective way for viability recovery is thawing in water at a temperature of +45°C, and then at +25°C followed by planting on a nutrient medium.